Self- Representation di Era Digital (Analisis Semiotika Acara TV Black Mirror Episode Nosedive) - Clarisa Tan; Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2019)
The rise of technology and information makes it easier for humans to communicate, introducing new aspects about the relationship between individual freedom and technology. Digital technology and social media are very influential in everyday life, communication between family and friends is not limited by geographical challenges. Social media makes it easier to express and understand ourselves through online communities. This research aims to see how self-representation in the digital era is shown through Netflix TV show Black Mirror episode Nosedive by Charlie Brooker. The reasercher conducted a semiotic analysis on the first episode in Season 3,